النزوع الفلسفي الجمالي في رواية ''روح البعد المفقود'' لإبراهيم الكوني - خلدي, أبو بكر; ملاحي, علي (جامعة الوادي - University of Eloued, 2021)
رواية ''روح البعد المفقود'' لإبراهيم الكوني، ''سيرة رؤيوية'' ذات نزوع وتوجه فلسفي، تتناول رؤيته الخاصة للأمور والظواهر. وتعالج جملة من التأملات الرؤيوية الفلسفية؛ كالجمال والهوية والعنف والاغتراب والحرية والموت. تنبثق من خلال هذه الحيثيات، الإشكالية النقدية الجوهرية لهذه الدراسة وهي: كيف تصور ''إبراهيم الكوني'' الجمال في روايته؟ والتي نصوغ منها جملة من الإشكاليات الفرعية: ماهي محددات الجميل والجمال عند الروائي؟ وكيف تتأسس رؤيته الفلسفية في ذلك؟ وما هي أبرز الملامح الفلسفية التي تتقاطع فيها رؤية إبراهيم الكوني الجمالية مع الفلسفة؟ تسعى هذه الدراسة الموسومة: ''النزوع الفلسفي الجمالي في رواية روح البعد المفقود لإبراهيم الكوني'' إلى الكشف عن ملامح فلسفة الجمال في -بعض من مقاطع الرواية- وخلاصة ما تتقاطعه مع الفلسفة ومن ثم معنى وفلسفة الجميل عنده، كما تتطرق لمبررات الحكم بالجمال وبالجميل على وجدانات إبداعية معينة يبوح بها النص، وهو ما يحيلنا الى ضرورة النبش في جوهر الاتجاه الذي يتبناه المتن الروائي على الصعيد الفلسفي والجمالي. The novel “The Spirit of the missing Dimension” by Ibrahim Al-Koni, is “a visionary biography”, with a philosophical tendency, it deals with his own vision of things and phenomena and many philosophical visionary reflections; such as beauty, identity, violence, alienation, freedom, and death. the fundamental problem of this study emerges: How does "Ibrahim Al-Koni" portray beauty in his novel? From which we formulate some sub-problems: What are the determinants of beauty for the novelist? How is his philosophical vision based on that? What are the most prominent philosophical features in which Ibrahim Al-Koni’s aesthetic vision intersects with philosophy? This study tagged: “The philosophical aesthetic tendency in the novel ‘‘The Spirit of the missing Dimension’’ by Ibrahim Al-Koni” seeks to show the features of the philosophy of beauty in - some of the novel’s passages - and what it intersects with philosophy and then the meaning and philosophy of the beauty to him, the study addresses the justifications for judging beauty on certain creative sentiments that the text reveals, which leads us to the necessity of digging into the essence of the direction adopted by the novelist text on the philosophical and aesthetic levels.
مقال
Keywords: النزوع الفلسفي ; الرؤية الفلسفية ; الجمال ; روح البعد المفقود ; إبراهيم الكوني; إبراهيم الكوني ; philosophical tendency ; philosophical vision ; beauty ; Ibrahim al-Koni